Interference effects in the photoelectron spectrum of the NeKr dimer and vibrationally selected interatomic Coulombic decay - Fedyk, Jacqueline; Gokhberg, Kirill; Miteva, Tsveta; Cederbaum, Lorenz S.; Kuleff, Alexander I. (Physical review, 2023)
In our work we study the interatomic Coulombic decay (ICD) in the NeKr dimer, where after 2s ionization of the Ne, the system relaxes and the excess energy is utilized to ionize the Kr. The temporal evolution of the ICD process in NeKr has been recently measured and theoretically explained by Trinter et al. [Chem. Sci. 13, 1789 (2022)]. Here we focus on two other main goals. The first goal regards the found interference effects in the photoemission (PE) spectrum, which are unusual phenomena in noble gas dimers. They result from the coherently excited vibrational energy levels and substantial dependence of the large ICD decay width on the internuclear distance. The PE spectrum reacts sensitively to changes in the potential energy curve (PEC) of the 2s ionized state, and we modified the available ab initio PEC in such a way that satisfactory agreement between theoretical and experimental data is achieved. The impact of isotope masses on the PE spectrum is briefly discussed and used in the determination of the PEC. Our second main goal concerns the nuclear motion during the ICD process. Here we investigate the impact of different vibrationally excited states of the electronic ground state on the ICD-electron and kinetic energy release (KER) spectra. To transfer our vibrationally selected ICD model to a realizable experiment, we also present the impact of temperature on the ICD-electron spectrum. Finally, our studies are complemented by comparing the directly computed KER spectrum to the mirror image of the ICD-electron spectrum, which coincide under certain conditions.
Gesehen am 17.05.2023